MODIFICĂRILE CANTITATIVE ȘI CALITATIVE ALE MICROBIOTEI INTESTINALE CA PREDICTOR PRECOCE AL CANCERULUI COLORECTAL - Leorda, Ana; Șeptițchi, Vladimir; Tolstenco, Dorina (CEP USM, 2024)
As a pressing global health problem, colorectal cancer (CRC) requires effective therapeutic strategies, and the underlying mechanisms remain an essential subject of investigation in this field. The problem of identifying some predictive markers of the probability of the appearance of this type of malignant neoplasms is quite current. Disturbance of the normal community of intes tinal bacteria represents an important problem in the development of CRC, thus new predictive markers of the probability of the appearance of this type of malignant neoplasms can be identi fied in changes in the qualitative and quantitative composition of the intestinal microbiota (MI). The subsequent development of preparations based on previously identified indigenous medicinal plants, which on the one hand have an anti-cancer effect, and on the other hand possess prebiotic properties, stimulate the multiplication of normal intestinal microbial flora. Targeted formation and maintenance of normal intestinal microbiota will be the basis for the development of new strategies in the prevention and treatment of CRC.
QUANTITATIVE AND QUALITATIVE CHANGES IN THE INTESTINAL MICROBIOTA AS AN EARLY PREDICTOR OF COLORECTAL CANCER
LEORDA, Ana, ȘEPTIȚCHI, Vladimir, TOLSTENCO, Dorina. Modificările cantitative și calitative ale microbiotei intestinale ca predictor precoce al cancerului colorectal. In: Integrare prin cercetare și inovare: conferința științifică națională cu participare internațională. Ştiinţe ale naturii și exacte, 9-10 noiembrie 2023. CEP USM, 2024, pp. 204-210. ISBN 978-9975-62-690-3.
Keywords: anti-cancer effect; colorectal cancer; intestinal microbiota